(3eNJUQ CfSGH GdQTGWis - (3ESeGYjd Hf EHQGgje GdHdHjSis; (3YHO Gddg Hf Ydj Hf YHO Gddg GddNej GdCfOdSj, CHh eMeO , GdQTGWj,J (B542 (3g` s
(3ChdgG (B:s
(3ef GdTjf hGdjGA s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B105 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B262s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B235 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs